2012
DOI: 10.1515/cclm-2012-0016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of capillary electrophoregram among heterozygous Hb Hope, Hb Hope/α-thalassemia-1 SEA type deletion and Hb Hope/β0-thalassemia

Abstract: The elevation of HbA(2) in patients with heterozygous Hb Hope and with Hb Hope/α-thalassemia-1 SEA type deletion measured by CE leads to incorrect β-thalassemia trait diagnosis. However, using CE electrophoregram together with levels of HbA(0), HbA(2) and Hb Hope would be a more accurate and precise method for diagnosis of Hb Hope/β(0)-thalassemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…19,20 One case of Hb Hope complex-SEA /αα showed mild microcytic hypochromic anemia, consistent with Pornprasert's report. 21 Although Hb Port Phillip has been documented on HbVar to cause hemoglobin instability due to loss of the heme interface, Hb Port Phillip heterozygotes alone in this study did not have significant manifestations of anemia and were only significantly anemic when combined with -SEA /αα, consistent with the findings of Du et al 17 Because Hb Port Phillip is rarely reported in the literature, the study of phenotype needs to be further accumulated. From the literature and our previous report, 22 Hb Mizuho caused severe hemolytic anemia because the mutated amino acid affected the binding of distal histidine β63 (E7) to the heme moiety.…”
Section: Dovepresssupporting
confidence: 84%
“…19,20 One case of Hb Hope complex-SEA /αα showed mild microcytic hypochromic anemia, consistent with Pornprasert's report. 21 Although Hb Port Phillip has been documented on HbVar to cause hemoglobin instability due to loss of the heme interface, Hb Port Phillip heterozygotes alone in this study did not have significant manifestations of anemia and were only significantly anemic when combined with -SEA /αα, consistent with the findings of Du et al 17 Because Hb Port Phillip is rarely reported in the literature, the study of phenotype needs to be further accumulated. From the literature and our previous report, 22 Hb Mizuho caused severe hemolytic anemia because the mutated amino acid affected the binding of distal histidine β63 (E7) to the heme moiety.…”
Section: Dovepresssupporting
confidence: 84%
“…An ameliorating effect of α-thalassemia interactions and high Hb F determinants has been well studied [40][41][42]. Moreover, the interaction of thalassemia and Hb variants has been reported in several publications in the Thai population such as compound heterozygosity for Hb Korle-Bu and Hb E with α + -thalassemia, complex interactions between Hb Lepore-Hollandia and Hb E with α + -thalassemia and interaction between Hb E and Hb Yala resulting in Hb E/β 0 -thalassemia, double heterozygosity of Hb Hope and α 0 -thalassemia and compound heterozygotes for Hb Hope and β 0 -thalassemia [43][44][45][46]. Hereditary persistence (HPFH) and δβ-thalassemia are characterized by elevated fetal hemoglobin levels in adult life.…”
Section: Interaction Of Common Thalassemia and Hemoglobin Variantsmentioning
confidence: 94%
“…The a-thalassemia-1 SEA and Thai type deletions were detected by using realtime PCR with SYBR Green1 high resolution melting (HRM) analysis as previously described [8]. Moreover, the molecular confirmation tests for Hb Hope and Hb CS were performed by using the amplification refractory mutation system (ARMS)-PCR analysis as reported elsewhere [6,9].…”
Section: Molecular Analysis For Diagnosis Of Thalassemia and Hemoglobmentioning
confidence: 99%
“…Asp, GGT [ GAT] is another unstable hemoglobin variant of the b-globin chain which is frequently found in the Thai population [3]. The co-inheritance of Hb Hope with a-thalassemia, b-thalassemia or Hb E [b26 (B8) Glu-[ Lys, GAG [ AAG] in Thai patients had been reported previously [4][5][6].…”
Section: Introductionmentioning
confidence: 99%